Phase fitted and amplification fitted of Runge-Kutta-Fehlberg method of order 4(5) for solving oscillatory problems - Salih, Mohammed M.; Ismail, Fudziah; Senu, Norazak (College of Science for Women/ University of Baghdad, 2020)
In this paper, the proposed phase fitted and amplification fitted of the Runge-Kutta-Fehlberg method were derived on the basis of existing method of 4(5) order to solve ordinary differential equations with oscillatory solutions. The recent method has null phase-lag and zero dissipation properties. The phase-lag or dispersion error is the angle between the real solution and the approximate solution. While the dissipation is the distance of the numerical solution from the basic periodic solution. Many of problems are tested over a long interval, and the numerical results have shown that the present method is more precise than the 4(5) Runge-Kutta-Fehlberg method.